Chemistry of Nucleic Acids - Lönnberg, Harri (De Gruyter Textbook, 2020)
Life in all its forms is based on nucleic acids which store and transfer genetic information. The book addresses the main aspects of synthesis, hydrolytic stability, solution equilibria of nucleosides and nucleotides as well as base modifications of nucleic acids. The author further describes their structural analogues used as therapeutic drugs, such as antivirals and anticancer agents, and prodrug strategies of nucleotides.